(untitled) (Research, Society and Development, 2022)
It was aimed, identified through the scientific literature as health education actions of nurses in the scope of Primary Health Care in the Assistance to Patients with Systemic Arterial Hypertension. This is an integrative literature review. The search was carried out in the Scientific Electronic Library Online, Latin American and Caribbean Literature on Health Sciences and Nursing Databases. Adherence to an academic training based on the biopsychic and spiritual model was identified, and a training strategy used to carry out nursing actions, such as educational and health promoting activities, through group education and lectures with guidance from education with the intuitive qualification of the patient’s habits, thus idealizing the adoption of practices of physical and healthy activities. Therefore, to make traditional health education more efficient, it is necessary to propose the model and integrate the user’s family, use audiovisual resources and carry out home visits.